2016
DOI: 10.1007/s11427-016-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SPOP with small molecules provides a novel strategy for kidney cancer therapy

Abstract: Renal cell carcinoma (RCC), accounting for 4% of all cancers, is the second most common cancer in urology. The most common form of RCC is clear cell RCC (ccRCC), with a ratio over 70%. Early-phase kidney diseases usually show rare symptoms in clinic; unfortunately, most patients are diagnosed with kidney cancer at the end stage, at which point the cancer is both resistant to chemotherapy and metastatic, thus leading to high mortality. Understanding cancer biology enables manipulation of disease targets by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…3 It has been reported that about 30% of patients with KIRC has already developed metastases at first diagnosis. 5 Therefore, to construct an effective prognostic prediction signature was of significant importance for the management of patients with KIRC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 It has been reported that about 30% of patients with KIRC has already developed metastases at first diagnosis. 5 Therefore, to construct an effective prognostic prediction signature was of significant importance for the management of patients with KIRC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, KIRC was resistant to radiotherapy and chemotherapy, 4 and surgery was the primary effective treatment method for localized KIRC, but had limited efficacy in advanced KIRC 3 . It has been reported that about 30% of patients with KIRC has already developed metastases at first diagnosis 5 . Therefore, to construct an effective prognostic prediction signature was of significant importance for the management of patients with KIRC.…”
Section: Introductionmentioning
confidence: 99%
“…Because kidney diseases are mostly asymptomatic during the early stages, many RCC patients are diagnosed with advanced stage metastatic diseases that are often resistant to chemotherapy, and therefore this is associated with high mortality 3. Despite the great advances made in the diagnosis and treatment of RCC, therapeutic options are limited and prognosis remains unfavorable 4.…”
Section: Introductionmentioning
confidence: 99%
“…SPOP expression correlates with a bad prognosis in ccRCC (163). Small molecules have been identified which inhibit SPOP-substrate protein interaction and suppress oncogenic SPOP signaling pathways in ccRCC (164).…”
Section: Micrornas Targeting E3-ubiquitin-ligasesmentioning
confidence: 99%